New perspectives on markers implicated in signalling pathways that advance diabetic nephropathy and its therapeutic approaches - Sharma, Rahul; Singh, Jaskaran (International Journal of Basic & Clinical Pharmacology, 2024)
Diabetic nephropathy is the chronic loss of kidney function occurring due to diabetes mellitus. Due to increased sugar levels, there is disfunctioning of glomeruli, loss of protein in urine, and decrease in the levels of serum albumin that mainly leads to edema. The progression of renal disfunctioning starts when glomerular filtration rate is greater than 90ml/min. A large body of evidence indicates that oxidative stress is the main attributor involved in the progression of macro-vascular complications of diabetes. (ROS), NAD(P)H oxidase, advanced glycation end products (AGE), polyol pathway, uncoupled nitric oxide synthase (NOS), mitochondrial respiratory chain via oxidative phosphorylation, protein kinase C, mitogen-activated protein kinases, cytokines and transcription factors eventually cause increased expression of extracellular matrix (EC) genes with progression to fibrosis and end stage renal disease. Apart from these well-established pathways, major markers in the kidney disease which could work as potential targets has been explored like MCP-1, BMP-7, p38 MAPK, MiR-130b, HSP-27, AKT which further needs more research as they have shown promising results in their early level of studies. The present review aims to investigate the molecular targets involved in diabetic nephropathy, and to comprehend the intricate signalling pathways, such as JAK/STAT, BMP-7–Smad1/5/8 pathway, RhoA/ROCK, caspases, to which the aforementioned markers have either an independent or dependent relationship. If these signalling pathways are properly studied, these markers may aid in the treatment of the disease and its associated secondary effects such as nephropathy.